2023
DOI: 10.1007/s00018-023-04912-7
|View full text |Cite
|
Sign up to set email alerts
|

The proper interplay between the expression of Spo11 splice isoforms and the structure of the pseudoautosomal region promotes XY chromosomes recombination

Teresa Giannattasio,
Erika Testa,
Monica Faieta
et al.

Abstract: XY chromosome missegregation is relatively common in humans and can lead to sterility or the generation of aneuploid spermatozoa. A leading cause of XY missegregation in mammals is the lack of formation of double-strand breaks (DSBs) in the pseudoautosomal region (PAR), a defect that may occur in mice due to faulty expression of Spo11 splice isoforms. Using a knock-in (ki) mouse that expresses only the single Spo11β splice isoform, here we demonstrate that by varying the genetic background of mice, the length … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 53 publications
(93 reference statements)
0
9
0
Order By: Relevance
“…Using a knock-in mouse model that expresses only SPO11β under its physiological promoter ( Spo11βki -only mouse) we confirmed that DSB frequency in the PAR changes with genetic background. Moreover, we observed that it fails more frequently in the Y-PAR than the X-PAR [ 30 ]. Furthermore, we demonstrated using the Spo11αki mouse model, that concomitant expression of SPO11α with SPO11β strongly boost formation of DSBs in the Y-PAR, regardless of the genetic background [ 30 ].…”
Section: Recombination-dependent Mechanism Of Chromosome Pairing and ...mentioning
confidence: 99%
See 4 more Smart Citations
“…Using a knock-in mouse model that expresses only SPO11β under its physiological promoter ( Spo11βki -only mouse) we confirmed that DSB frequency in the PAR changes with genetic background. Moreover, we observed that it fails more frequently in the Y-PAR than the X-PAR [ 30 ]. Furthermore, we demonstrated using the Spo11αki mouse model, that concomitant expression of SPO11α with SPO11β strongly boost formation of DSBs in the Y-PAR, regardless of the genetic background [ 30 ].…”
Section: Recombination-dependent Mechanism Of Chromosome Pairing and ...mentioning
confidence: 99%
“…Moreover, we observed that it fails more frequently in the Y-PAR than the X-PAR [ 30 ]. Furthermore, we demonstrated using the Spo11αki mouse model, that concomitant expression of SPO11α with SPO11β strongly boost formation of DSBs in the Y-PAR, regardless of the genetic background [ 30 ]. Therefore, it can be concluded that the expression of the single SPO11β isoform increases the risk of XY asynapsis.…”
Section: Recombination-dependent Mechanism Of Chromosome Pairing and ...mentioning
confidence: 99%
See 3 more Smart Citations